Terbentuknya Identitas Fans Sepak Bola sebagai Budaya Massa dalam Industri Media - Syahputra, Iswandi (Universitas Negeri Yogyakarta, 2016)
Nowadays football is not merely sport. It has become industry, even popular culture. This happen because on the same time mass media grows into mass culture industry. The union of football and mass media as industry has melted few social and culture boundaries. Socially